Analisis Mutu Soyghurt Edamame Sebagai Makanan Pendamping Alternatif Penderita Stunting - Rusdianto; Yoan Melly Nurrahma; Lailatul Mardhiyyah; Moh Nu’man Ash-Shiddieqiey Ash-Shiddieqiey; Tsabitah Amaliyah Amaliyah; Anastasya Eka Saputri (Gema Wiralodra, 2022)
Stunting is a condition of growth and development of a body that is shorter than its age. Stunting sufferers need complementary foods that contain high nutrition to help reduce the risk of deadly disease or the risk of death. One of the alternative complementary foods that is good for stunting sufferers is edamame soyghurt. The purpose of this study was to determine the quality of edamame soyghurt as an alternative complementary food for stunting sufferers. The experimental design used was a completely randomized design (CRD) with different combinations of treatments on edamame juice, skim milk, and starter. The combination of different treatments gave a significant effect on the results of the test parameters pH, total BAL, and acidity. Treatments that have the potential as alternative complementary foods for stunting sufferers are treatment C with test results at pH test parameters of 4.3; total BAL 1.1 x 10^5 CFU/ml; acidity 1.2306%.